Novel inhibitors of the condensing enzymes of the type II fatty acid synthase of pea (Pisum sativum). - Jones, A L (2000)
The type II fatty acid synthases (FASs) of higher plants (and Escherichia coli) contain three condensing enzymes called beta-ketoacyl-ACP synthases (KAS), where ACP is acyl-carrier-protein. We have used novel derivatives of the antibiotic thiolactomycin to inhibit these enzymes. Overall de novo fatty acid biosynthesis was measured using [1-(14)C]acetate substrate and chloroplast preparations from pea leaves, and [1-(14)C]laurate was used to distinguish between the effects of the inhibitors on KAS I from those on KAS II. In addition, the activities of these enzymes, together with the short-chain condensing enzyme, KAS III, were measured directly. Six analogues were tested and two, both with extended hydrocarbon side chains, were found to be more effective inhibitors than thiolactomycin. Incubations with chloroplasts and direct assay of the individual condensing enzymes showed that all three compounds inhibited the pea FAS condensing enzymes in the order KAS II > KAS I > KAS III. These results demonstrate the general activity of thiolactomycin and its derivatives against these FAS condensation reactions, and suggest that such compounds will be useful for further detailed studies of inhibition and for use as pharmaceuticals against Type II FASs of pathogens.